Website Design as an Online Trading Media at the "Coffee On The Way" Shop - Ibrahim, Herland; Azhar, Pahrezi; Martikasari, Arida (Journal of Engineering Science and Technology Management (JES-TM), 2025)
An implementation of the e-commerce website at the Coffee on the Way store described in this report was identified with the aim of knowing that by designing and implementing a website for the trade, it can build digitalization of online trade so that it will be described in detail how the e-commerce website design process for the Coffee on the Way store. The media that will be used to analyze how the system works is with flow maps and information tables. Therefore, the design to build the website uses DFD level 0-1 and PDM and CDM for database design and menu structure to identify the system navigation menu. Based on the findings of the implementation that has been carried out, there are several external software used such as XAMPP, bootstrap, leaflet and so on. The results of the implementation on the website are that the website system can display designs and features that have been previously designed in a concrete manner. Therefore, the contribution of the website is successfully displaying the planned features and designs and enabling the online transaction in the website.